Sistem Informasi Geografis (SIG) Pemetaan Baliho dan Billboard di Kota Bengkulu (CV. Tunggal Abadi) Berbasis Android - Ardi Wijaya; Teguh Wibowo; Rozali Toyib; M. Husni Rifqo (UNIVED Press, 2022)
Abstract— This Geographic Information System can be employed by users using Android-based mobile devices so that they can provide roles and functions to consumers in the form of information related to the installation location of billboards and billboards managed by CV. Tunggal Abadiand its search menu.This application is created using the Best First Search algorithm. The results of this study indicate that the Best First Search Algorithm can be applied in tracing the location of the installation of billboards and billboards for CV. Tanggal Abadi.The resulting application can provide convenience in rinsing the location for installing billboards and billboards for CV. Tunggal Abadi and can be used on the Android platform and based on tests carried out by distributing questionnaires to 10 respondents. Viewing from the results of the average answers, respondents who reached 53% answered strongly agree, 26% agree, 14% disagree, and 14% disagree. So from the results of data processing, it can be concluded that this system is feasible to use. Keyword: Geogiaphic Information System, Best First Search Algorithm, CV. Tanggal Abadi